Preliminary study on cyanobacteria composition and selected water quality parameters from freshwater fish (tor tambroides) ponds in Serian, Sarawak - Harith, Mohd Nasarudin; Hassan, Ruhana (2007)
Toxic cyanobacteria, for example, species from the genera Microcystis,Anabaena and Oscillatoria may present risk of cyanotoxin bioaccumulation in fish tissues either directly or via other organisms in the food web, consequently posing hazard to aquatic animals and humans. A study was conducted to determine cyanobacterial species composition and their relationships with selected water quality parameters. Water samples were collected from subsurface of two Tor tambroides (locally known as empurau) aquaculture ponds in Serian District, Sarawak from January to June 2007. There were 35 cyanobacterial species recorded from 11 genera of four families. Common occurrence of Chroococcus, Nostoc, Oscillatoria, Pleurocapsa and Synechocystis genera were observed in both ponds. In Pond P12, visible brownish bloom which consists of Microcystis and Anabaena were observed. The correlation ccr-efficient analysis in Pond AP22 showed that cyanobacterial cell density has significant positive correlation with biological oxygen demand (r =0.839, p<O.01). Chlorophyll a concentration showed significant positive correlation with turbidity in both ponds (r =0.861, r<O.01 in Pond AP22 and r =0.849, p<0.01 in Pond P12). Further research should be carried out to determine the presence of cyanotoxin in those aquaculture ponds.